Legal Certainty In Taxation Policy: A Literature Review On Administrative Sanctions In Value Added Tax Compensation Corrections - Bram Sostenes; Prianto Budi Saptono (Eduvest - Journal of Universal Studies, 2025)
Legal uncertainty in the implementation of tax policy poses a serious challenge to efforts aimed at improving compliance and the legitimacy of the tax system. One key issue arises in the application of administrative sanctions as stipulated in Article 13 paragraph (3) of the General Tax Provisions and Procedures Law (UU KUP), particularly in the context of corrections to overpaid Value Added Tax (VAT) compensation. This article presents a literature review to analyse how these administrative sanction policies are interpreted and applied, as well as their implications for the principle of legal certainty. Through a review of selected scholarly sources, this article finds that multiple interpretations of legal norms trigger recurring tax disputes, create litigation burdens, and erode taxpayer trust in the tax administration system. The evaluation shows that the automatic imposition of surcharge sanctions on corrections of overpaid VAT compensation, without actual fiscal loss, is often viewed as disproportionate. This article recommends the importance of regulatory harmonization, improved clarity of legal norms, and the adjustment of audit guidelines to align with the principle of legal certainty, in order to support a fairer and more effective tax governance.